Characterization of the mitochondrial genome of Rousettus leschenaulti. (December 2014) - Szcześniak, Michał; Yoneda, Misako; Sato, Hiroki; Makałowska, Izabela; Kyuwa, Shigeru; Sugano, Sumio; Suzuki, Yutaka; Makałowski, Wojciech; Kai, Chieko
Abstract We present a complete sequence of mitochondrial genome of echolocating megabat Rousettus leschenaulti (16, 704 nt, GenBank record KC702803) and provide its annotation. We also show that phylogenetic analysis based on mitochondrial genomes of eighteen bat species, including R. leschenaulti, supports division of Chiroptera into Yinpterochiroptera and Yangochiroptera.